2000
DOI: 10.1111/j.2042-7174.2000.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists' attitudes towards research

Abstract: Objectives — To investigate community pharmacists' perception of Pharmacy Practice research and to identify perceived barriers preventing their participation in research. Method — A self‐completed postal questionnaire, including 29 attitudinal statements was analysed using factor analysis. Setting — The study group comprised pharmacists working in all 651 community pharmacies in East London and Essex. Key findings — The response rate was 60 per cent. Factor analysis revealed five factors comprising correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 10 publications
8
60
0
Order By: Relevance
“…While Knapp et al [5] reported a project growth in pharmacy education and research in faculties of pharmacy in the United States (US), few studies have reported the perspectives of practising pharmacists. Surveys of community pharmacists in the UK and pharmacists in Australia identified that respondents perceived practice research to be important and relevant but were less likely to participate themselves with confidence, lack of payment, time and opportunities cited as major barriers [6,7]. Similar findings have been reported for other health professional groupings of social workers [8,9], allied health professionals [10], speech-language pathology practitioners [11], physicians and nurses [12,13].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…While Knapp et al [5] reported a project growth in pharmacy education and research in faculties of pharmacy in the United States (US), few studies have reported the perspectives of practising pharmacists. Surveys of community pharmacists in the UK and pharmacists in Australia identified that respondents perceived practice research to be important and relevant but were less likely to participate themselves with confidence, lack of payment, time and opportunities cited as major barriers [6,7]. Similar findings have been reported for other health professional groupings of social workers [8,9], allied health professionals [10], speech-language pathology practitioners [11], physicians and nurses [12,13].…”
Section: Introductionsupporting
confidence: 67%
“…• key published literature on research related interests, attitudes and skills of health professionals [6][7][8][9][10][11][12][13]. • The Roberts' Review, a United Kingdom review of the supply of people within science, technology and engineering, which defines competencies around different levels of research participation [16].…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…Studies during this period indicated increased awareness and positive attitude towards research among pharmacists, mostly in the community setting (Rosenbloom et al 2000;Simpson et al 2001;Saini et al 2006;Armour et al 2007;Peterson et al 2009). Future development of community pharmacy practice and new practice models could be among the motivational factors for this trend.…”
Section: -2009mentioning
confidence: 92%
“…There is evidence that these research networks will increasingly augment pharmacists' active participation in practice-based research (Carr et al 2011;Hébert et al 2013;Peterson et al 2009;Rosenbloom et al 2000). Furthermore, studies have investigated pharmacists' attitudes and willingness to participate in PBRNs (Carr et al 2011;Hébert et al 2013;Rosenbloom et al 2000) and others have discussed the importance of PBRNs (Peterson et al 2009;Rosenbloom et al 2000;Simpson et al 2001).…”
Section: Pharmacists' Attitudes Towards Practice-basedmentioning
confidence: 96%
See 1 more Smart Citation